Peningkatan Hasil Belajar Gerak Pencak Silat melalui Media Audiovisual dan Garis 8 Penjuru pada Siswa Kelas V SD Negeri 1 Rendang Tahun Pelajaran 2024/2025 - I Kadek Junaedi Putra; Kadek Yogi Parta Lesmana; Made Agus Wijaya (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to improve learning outcomes in variations of non-locomotor movements in horse stances and locomotor movements in pencak silat steps using audio-visual media. The learning outcomes in attitude assessment showed a significant improvement, from a class average score of 85 in Cycle I to 89.86 in Cycle II and 92.83 in Cycle III. The learning outcomes in knowledge assessment showed a significant increase, from a class average score of 78 in Cycle I to 86.72 in Cycle II and 92.83 in Cycle III for fifth-grade students at the Education Unit of SD Negeri 1 Rendang, Karangasem Regency, in the 2024/2025 academic year. This study is a classroom action research study conducted in three cycles. The subjects were 29 fifth-grade students at the Education Unit of SD Negeri 1 Rendang in the 2024/2025 academic year. The results showed that the learning completion percentage increased from 65% in Cycle I to 97% in Cycle II and 97% in Cycle III. Meanwhile, learning outcomes in the skills assessment showed a significant improvement, with a class average score of 82 in Cycle I, rising to 87.75 in Cycle II and 88.62; and a learning completion percentage of 65% in Cycle I, rising to 97% in Cycle II and 97% in Cycle III. In conclusion, learning outcomes for variations in non-locomotor movements in horse stances and locomotor movements in Pencak Silat steps in Karangasem Regency in the 2024/2025 academic year were improved through audio-visual media and the 8-point line aid. Keywords: 8-Way Compass, Learning Outcomes, Locomotor, Non-Locomotor, Pencak Silat, Movement Variations